A phytosociological survey of aquatic vegetation in the main freshwater lakes of Greece - D. Zervas; I. Tsiripidis; E. Bergmeier; Tsiaoussi, V. (2020)
Zervas D, Tsiripidis I, Bergmeier E, Tsiaoussi V (2020) A phytosociological survey of aquatic vegetation in the main freshwater lakes of Greece. Vegetation Classification and Survey 1: 53-75. https://doi.org/10.3897/VCS/2020/48377